Combined analytical-numerical methodologies for the evaluation of mixed-mode (I + II) fatigue crack growth rates in structural steels. (November 2017) - Silva, A.L.L.; de Jesus, A.M.P.; Xavier, J.; Correia, J.A.F.O.; Fernandes, A.A.
Highlights: Stress intensity factors (SIFs) are evaluated for fatigue cracks propagating under pure mode I and mixed-mode I + II. Compact tension (CT) specimens with a side hole are proposed to generate a stress field ahead of the crack tip yielding mixed-mode fatigue crack propagation. Digital image correlation (DIC) is used to assess mode I and mode II SIF from full-field displacement measurements. DIC data was used to directly estimate the crack tip location during the fatigue tests. Finite element simulations are carried out to corroborate the proposed methodology. Abstract: This paper proposes an experimental study aiming to evaluate stress intensity factors (SIFs) for fatigue cracks propagating under pure mode I and mixed-mode I + II for a S235 structural steel. Compact tension (CT) specimens with a side hole were manufactured in order to generate a stress field, ahead of the crack tip, resulting in mixed-mode fatigue crack propagation. Specimens with distinct side hole locations were submitted to fatigue tests under stress controlled conditions for a stress ratio, R = 0.01. Fatigue tests were coupled with digital image correlation (DIC) to assess mode I and mode II SIF from full-field displacement measurements. Besides, DIC data was used to directly estimate the crack tip location during the test. A validation study was carried out by comparing this approach with regard to conventional optical measurements. Finite element simulations were also performed to validate the crack branching models and direct identification of SIF values. The proposed DIC approach was demonstrated to be an efficient tool for the automation of crack path detection and stress intensity factors computation. Mixed-mode fatigue crack data correlated well with pure mode I fatigue crack propagation data using the Paris law and an effective stress intensity factor as proposed by Tanaka.